PENGUATAN PENGETAHUAN REMAJA TENTANG PENYAKIT MENULAR MELALUI PROGRAM EDUKASI PARTISIPATIF - Puspita, Rina; resti; AP Wangi, Gracellda; R Anshori, Faisal (Jurnal Pengabdian Multidisiplin dan Pemberdayaan Masyarakat, 2025)
Adolescents are an age group that is vulnerable to infectious diseases, especially sexually transmitted infections (STIs), due to lack of knowledge and awareness of risky behavior. This activity aims to improve adolescents' knowledge through an interactive and contextual participatory education approach. The methods used include an initial survey (pre-test), delivery of educational materials, social simulation, reflection, and final evaluation (post-test). The activity was conducted with 40 high school students by actively involving them in the learning process. The results showed significant improvements in the aspects of knowledge, prevention methods, and risk awareness, with an average score increase of 30.3%. The active participation and positive responses of the participants reflect the effectiveness of the participatory approach in shaping deeper understanding. The preliminary conclusion is that participatory education is an effective strategy in strengthening adolescents' health literacy and can be part of long-term preventive efforts in tackling infectious diseases.